El liberalismo político en Michoacán, 1851-1861 - Mercado Villalobos, Alejandro (Universidad Michoacana de San Nicolás de Hidalgo, 2008)
In the old western world, the individual freedom was considered by some as a natural right, and for other, like a negation to the collective freedom. In Greece, Pericles defended the concept of equality and individualism, while Plato alleged that it was unnecessary the existence of an egalitarian society; in The Republic, it attacked the concept of equality among the men pointing out that the institutions, once created, they were outside of all critic and improvement. Although not so severe, Aristotle also supported the existence of non egalitarian societies, in the sense of the permanency of a ruling elite and of the chimera of a social foundation of political collective participation. In the Roman empire, the concept Individualism, one of the central elements of the liberalism decimonónico in the western world, took form in the Laws of the Twelve charts, in first o'clock of these the null privilege acceptance settled down some in favor of anybody and it instituted the law like common contract for all the citizens, without range distinction.1 although this independent character gave form to the Roman State, starting from Justiniano, and much more from Constantino, the individualistic tradition it declined enough, thank you partly to the Christianity that originated a time of ignorant intolerance, and although he/she sat down the bases of an individualistic faith, it put an end to the old practice of the thought freedom and religious tolerance, ironically, the Christianity transmitted the vision universalista and individualist, elements of the liberal tradition.2 the examples of Greece and Rome are clear in the sense that from the antiquity you discussed, among other things, the forms of social coexistence as for the man's rights, a thought that remained effective until the arrival of the English and French ideologists who you/they took charge of to renovate the ideas and to advance in new forms of social convenience

En el mundo antiguo occidental, la libertad individual era considerada por algunos como un derecho natural, y por otros, como una negación a la libertad colectiva. En Grecia, Pericles defendió el concepto de igualdad e individualismo, mientras que Platón alegaba que era innecesaria la existencia de una sociedad igualitaria; en La República, atacó el concepto de igualdad entre los hombres señalando que las instituciones, una vez creadas, quedaban fuera de toda crítica y mejoramiento. Aunque no tan severo, Aristóteles apoyó también la existencia de sociedades no igualitarias, en el sentido de la permanencia de una elite gobernante y de la quimera de un fundamento social de participación política colectiva. En el imperio romano, el concepto Individualismo, uno de los elementos centrales del liberalismo decimonónico en el mundo occidental, tomó forma en las Leyes de las Doce tablas, en la primera de estas se estableció la nula aceptación de privilegio alguno a favor de nadie y instituyó la ley como contrato común para todos los ciudadanos, sin distinción de rango.1 Aunque este carácter independiente dio forma al Estado romano, a partir de Justiniano, y mucho más desde Constantino, la tradición individualista declinó bastante, gracias en parte al cristianismo, que originó una época de intolerancia ignorante, y aunque sentó las bases de una fe individualista, puso fin a la antigua práctica de la libertad de pensamiento y tolerancia religiosa, irónicamente, el cristianismo transmitió la visión universalista e individualista, elementos de la tradición liberal.2 Los ejemplos de Grecia y Roma son claros en el sentido de que desde la antigüedad se discutieron, entre otras cosas, las formas de convivencia social en cuanto a los derechos del hombre, un pensamiento que permaneció vigente hasta la llegada de los ideólogos ingleses y franceses, quienes se encargaron de renovar las ideas y avanzar en nuevas formas de conveniencia social.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; IIH-M-2008-0008; Opción en historia de México; Liberalismo político; Michoacán; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2376